LEARNING ASSESSMENT FOR CHILDREN WITH SPECIAL NEEDS IN INCLUSIVE EARLY CHILDHOOD EDUCATION (BELIA: Early Childhood Education Papers, 2022)
The objective of this study was to explain the learning assessment for children with special needs in the inclusion institution of Talenta Kindergarten in Semarang as well as several supporting and inhibiting factors regarding the assessment. The type of research used for this study was qualitative, it was when the researcher described the findings based on the actual conditions in the reality and compared it to the existing theories. The result showed that regarding the teachers’ way in conducting learning assessments, there were three stages, namely 1) the planning stage which included initial observations, designing learning programs that were adjusted to the basic competencies; 2) the implementation stage which was the process of implementing the assessment (observation, performance, and interview), continuity, and the assessment tools; 3) the documentation stage which was reporting the results of assessment. Factors that were supporting the learning assessment were institutional support in the form of providing training programs for the teachers, the availability of information about the proces and learning outcomes from parents and the results of children’s therapy that would be used as reference for the teachers. Meanwhile, the inhibiting factors for the learning assessment were the lack of parental cooperation in providing children’s data so that the assessment could not be conducted properly, the limited space and time of teachers during online learning so that not all of the children’s learning activities could be seen directly, and teachers’ fatigue during their taking home visit caused the learning time was shorter and the assessment was not accurate. Keywords: learning assessment, inclusion, children with special needs